Think crime! Using evidence, theory and crime prevention through environmental design (CPTED) for planning safer cities - Cozens, Paul (Praxis Education, 2016)
"Think Crime! is aimed at both beginners and expert crime prevention professionals. Along with its practical nature, the book is also structured as a text book for a 12-week course on CPTED. This course would be appropriate for students, crime prevention and security professionals, urban planners, architects, Police, facilities managers, sustainable development specialists, and local governments. Create effective CPTED programs that can be justified by using the deeper understanding provided in Think Crime! The author shows how the use of crime data, crime risk assessment, mapping criminal opportunities, fear of crime data, and theories of environmental criminology can suppport better crime prevention outcomes and policies and improved urban planning solutions, public health and sustainable development outcomes." --- Publishers website